Marathon Running Increases Synthesis and Decreases Catabolism of Joint Cartilage Type II Collagen Accompanied by High-Energy Demands and an Inflamatory Reaction - Hernández-Hermoso, José A.; Nescolarde, Lexa; Roca, Emma; Revuelta-López, Elena; Ara, Jordi; Bayes-Genis, Antoni (Frontiers in Physiology, 2021)
Objective: To determine the effect of marathon running on serum levels of inflammatory, high energy, and cartilage matrix biomarkers and to ascertain whether these biomarkers levels correlate. Design: Blood samples from 17 Caucasian male recreational athletes at the Barcelona Marathon 2017 were collected at base line, immediately and 48h post-race. Serum C reactive protein (CRP), creatin kinase (CK) and lactate dehydrogenase (LDH) were determined using an AU-5800 chemistry analyser. Serum levels of hyaluronan (HA), cartilage oligomeric matrix protein (COMP), aggrecan chondroitin sulphate 846 (CS846), glycoprotein YKL-40, human procollagen II N-terminal propeptide (PIINP), human type IIA collagen N-propeptide (PIIANP) and collagen type II cleavage (C2C) were measured by sandwich enzyme-linked immune-sorbent assay (ELISA). Results: Median sCK and sLDH levels increased (3-fold, 2-fold) post-race (429 (332)U/L, 323 (69)U/L) (P<0.0001; P<0.0001) and (6-fold, 1.2-fold) 48h post-race (658 (1073)U/L, 218 (45)U/L) (P<0.0001; P<0.0001). Median sCRP increased (10-fold) after 48h post-race (6.8 (4.1)mg/L) (P<0.0001). Mean sHA levels increased (4-fold) post-race (89.54 ± 53.14ng/mL) (P<0.0001). Mean sPIINP (9.05 ± 2.15ng/mL) levels increased post-race (10.82 ± 3.44ng/mL) (P=0.053) and 48h post-race (11.00 ± 2.96ng/mL) (P=0.001). Mean sC2C levels (220.83 ± 39.50ng/mL) decreased post-race (188.67 ± 38.52ng/mL) (P=0.002). In contrast, mean sCOMP, sCS846, sPIIANP and median sYKL-40 were relatively stable. We found a positive association between sCK levels with sLDH pre-race (r=0.758, P<0.0001), post-race (r=0.623, P=0.008) and 48h post-race (r=0.842, P<0.0001); sHA with sCRP post-race vs 48h post-race (r=0.563, P=0.019) and sPIINP with sCK pre-race vs 48h post-race (r=0.499, P=0.044) and with sLDH 48h post-race vs post-race (r=0.610, P=0.009) and a negative correlation of sPIIANP with sCRP 48h post-race (r=-0.570, P=0.017). Conclusion: Marathon running is an exercise with high-energy demands (sCK and sLDH increase) that provokes a high and durable general inflammatory reaction (sCRP increase) and an immediately post-marathon mechanism to protect inflammation and cartilage (sHA increase). Accompanied by an increase in type II collagen cartilage fibrils synthesis (sPIINP increase) and a decrease in its catabolism (sC2C decrease), without changes in non-collagenous cartilage metabolism (sCOMP, sC846, sYKL-40). Metabolic changes on sPIINP and sHA synthesis may be related to energy consumption (sCK, sLDH) and the inflammatory reaction (sCRP) produced.